The European Union's CBAM as a de facto Climate Club: The Governance Challenges - Szulecki, Kacper; Overland, Indra; Smith, Ida Dokk (Frontiers in Climate, 2022)
The European Commission has announced far-reaching reforms to accelerate the reduction of greenhouse gas emissions. Among the proposals constituting the European Green Deal is the adoption of a Carbon Border Adjustment Mechanism (CBAM) to prevent carbon leakage. In practice, however, CBAM will not only act as a shield for the European Emissions Trading System (ETS) but also incentivize other countries to implement compatible carbon pricing schemes. We argue that the EU’s CBAM thus de facto has the features of a climate club, but the current proposals and debate do not address how the club would be governed. While the literature focuses on legal and economic aspects of CBAM design, there is little debate about the governance challenges it entails. We identify two major challenges. CBAM will put pressure on trade partners to introduce carbon pricing and/or bring it into line with the price of EU ETS allowances. However, the future availability and thus price of ETS allowances is determined within the EU. Secondly, the method for calculating embedded carbon is left to the discretion of the European Commission. EU policymakers need to acknowledge the challenges that follow from setting up a de facto climate club, and that addressing them involves a trade-off between maintaining control over the direction and ambition of climate policy and CBAM’s legitimacy.